2010
DOI: 10.2202/1548-923x.1940
|View full text |Cite
|
Sign up to set email alerts
|

Preceptor Preparation: An Investment in the Future Generation of Nurses

Abstract: Nurse preceptors fulfill a primary role in the success of preceptorship experiences during the education of student nurses in their final year of study. Evidence suggests that this success depends greatly on adequate preceptor role preparation and support. The purposes of this qualitative, descriptive study were to explore and describe preceptor role support and development within the context of a rural and northern mid-sized Canadian community. More specifically, in this study the following are described: pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 0 publications
5
27
1
Order By: Relevance
“…Preceptor effectiveness is a large focus in nursing research, as it is an extensive process. Luhanga, Dickleson, and Mossey (2010) aimed to explore and describe preceptor role support and development within a mid-sized Canadian hospital. A qualitative exploratory and descriptive design was used to gauge preceptors' feelings of effectiveness and development.…”
Section: Preceptor Effectivenessmentioning
confidence: 99%
“…Preceptor effectiveness is a large focus in nursing research, as it is an extensive process. Luhanga, Dickleson, and Mossey (2010) aimed to explore and describe preceptor role support and development within a mid-sized Canadian hospital. A qualitative exploratory and descriptive design was used to gauge preceptors' feelings of effectiveness and development.…”
Section: Preceptor Effectivenessmentioning
confidence: 99%
“…This is supported in previous literature. [8,29] Preceptor as protector of self and professional ethos, however, is new and unexplored in the nursing literature. Although exciting, it is also somewhat unexpected as professional core values are fundamental to the discipline of nursing and are identified by the AACN [64] and the NLN.…”
Section: Discussionmentioning
confidence: 99%
“…[26,27] Nurses serving as preceptors should have clear responsibilities established in order to help prepare them for the role. [28] Preceptors themselves have stressed the need for clearer role expectations, guidance, and support; [17,29] however, preceptors have reported that they feel ill-prepared to assume the role. [13,30,31] Kowalski et al [15] suggest that a lack of preparation is a reason for burnout and dissatisfaction with nurses working as preceptors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations